Pengembangan Media Pohon Bilangan dalam Pembelajaran Matematika Materi Perkalian pada Siswa Kelas III SD Negeri Kadongdong Kabupaten Tangerang - Yuliadi, Ryan; Nurhayati, Siti; Bahri, Syaeful (Lembaga Yasin AlSys, 2021)
Ryan Yuliadi 1786206233 Development Of Number Tree Media In Mathematics Learning Multiplication Material For Third Grade Student At SD Negeri Kadongdong Tangerang Regency. This development research was carried out in class III at SDN Kadongdong Tigaraksa District, Tangerang Regency based on the problem of not understanding multiplication material so that the researchers aimed to produce a product in the form of Number Tree Media in Mathematics Learning Multiplication Material Theme 1 (Growth and Development of Living Things) Subtheme 3 (Animal Growth ) Lesson 1 In Class III Sdn Kadongdong. This research is a research and development (R&D) research which refers to the ADDIE development model which consists of: (1) Analysis (Analyze), (2) Design, (3) Development, (4) Implementation (implementation). ), (5) Evaluation (evaluation). The instrument used to measure the quality of the number tree media is the assessment sheet of material experts, media experts, and student responses. Based on the assessment of the validity of the number tree media, the results are very feasible. Material experts gave a rating of 77.5% with a